PENGARUH DUKUNGAN MANAJEMEN PUNCAK, BUDAYA ORGANISASI, DAN KEMAMPUAN PENGGUNA SISTEM INFORMASI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA PT. BANK ACEH SYARIAH KANTOR PUSAT OPERASIONAL - Arif Muttaqin; Yulia Fitri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study was to determine and analyze the effect of top management support, organizational culture and the ability of users of information systems on the performance of accounting information systems at PT. Bank Aceh Syariah operational head office. This type of research is causal associative with census sampling method on 36 employees of PT. Bank Aceh Syariah KP. Operational. Data was collected using a questionnaire. The results of data analysis using multiple linear regression analysis techniques. The results of the study indicate that top management support and the ability of users of information systems partially have a significant effect on the performance of accounting information systems. Meanwhile, organizational culture partially has no effect on the performance of accounting information systems. However, simultaneously top management support, organizational culture and the ability of users of information systems have a significant effect on the performance of accounting information systems at PT. Bank Aceh Syariah KP. Operational (sig. 0.000 0.05). Therefore, the PT. Bank Aceh Syariah KP. Operations are expected to further improve the support of top management, the ability of users of information systems, and organizational culture in order to achieve good accounting information system performance.